Adenosine Downregulates the Activities of Glutamatergic Neurons in the Paraventricular Hypothalamic Nucleus Required for Sleep - Chen, Changlin; Lin, Yichen; Cai, Feng; Li, Jinsui; Li, Haixun; Li, Xiantao (Frontiers in Neuroscience, 2022)
Adenosine is an endogenous substance that regulates sleep homeostasis. It plays an important role in sleep induction under physiological condition. So far, the neural mechanisms underlying sleep-promoting effects of adenosine are not completely clear. Recent studies have shown that glutamatergic neurons in the paraventricular hypothalamic nucleus (PVH) play an important role in wakefulness. Using whole-cell patch-clamp, we found that adenosine can inhibit glutamatergic neurons in PVH. This inhibition is mainly achieved by activating adenosine type 1 receptors, thereby reducing hyperpolarization-activated cyclic nucleotide-gated cation channels. By recording electroencephalogram (EEG) and electromyography (EMG), it was found that local administration of adenosine type 1 receptor blocker in PVH could significantly reduce the NREM sleep. On the contrary, if adenosine was given, it could increase the NREM sleep. These results suggest that adenosine can promote sleep by reducing the excitability of PVH neurons. This findings reveal a novel mechanism of adenosine regulating sleep homeostasis.